Tinjauan Yuridis Hak Cipta Sebagai Objek Jaminan Fidusia Menurut Uu No 42 Tahun 1999 Tentang Jaminan Fidusia - Ilham Permana (INVENTION: Journal of Intellectual Property Law, 2025)
The aim of this research is to see whether Copyright can be used as an Object of Fiduciary Guarantee according to Law no. 42 of 1999 concerning Fiduciary Guarantees and knowing the factors causing the non-implementation of Copyright as Fiduciary Guarantee. This research uses the Normative Empirical method that examines the implementation of positive legal provisions (legislation) and written documents in action (factual) on each specific legal event that occurs in society. With the aim of ensuring whether the results of the application of the law are in accordance or not in accordance with the provisions of the statutory regulations. The results of this research are that copyright may be used as an object of Fiduciary Guarantee according to Law Number 42 of 1999 concerning Fiduciary Guarantee where copyright can be encumbered with collateral in the form of a fiduciary, but not on the object encumbered by the copyright, but rather the economic value attached to it. the copyright. Apart from that, the Copyright must first be registered with the Directorate General of Intellectual Property of the Ministry of Law and Human Rights before it can be guaranteed. This is important because it is proof of ownership and registration of the Copyright holder. And regarding the implementation of Copyright as Fiduciary collateral, it is still hampered by several factors that make this regulation unable to be implemented, including regulatory obstacles, where the Indonesian Bank regulations indicate that Intellectual Property has not been registered as collateral, property appraisal, which in government regulation number. 24 of 2022 concerning the Creative Economy does not yet technically regulate the protection and procedures for receiving collateral, and Indonesian society's appreciation for Copyright is still very lacking and many people still don't even know that Copyright can be used as an object of fiduciary collateral.